ANALGESIC EFFECT OF “DINH THONG PHONG” CAPSULES ON EXPERIMENTAL ANIMALS - Tran Thanh Tuan,; Vu Ngoc Thang,; Dao Nguyen Manh,; Quach Thi Quynh,; Nguyen Hai Duong,; Dang Thi Minh, (Tạp chí Y học Quân sự, 2024)
Purpose: Evaluate the analgesic effect of “Dinh Thong Phong” capsules on experimental animals. Subjects and Methods: “Dinh Thong Phong” capsules, meeting the standard criteria, were evaluated for analgesic effect on white mice. In particular, the central analgesic effect was assessed using the hot plate model, peripheral analgesic effect was assessed using the writhing pain model. Results: In the hot plate model, “Dinh Thong Phong” capsules at a dosage of 860 mg/kg and 2,580 mg/kg significantly increased the reaction time to heat (p < 0.001) compared to the control group. The difference in reaction time to heat between the groups using “Dinh Thong Phong” capsules and the group using codeine phosphate at a dose of 20 mg/kg was not statistically significant (p > 0.05). In the writhing model, “Dinh Thong Phong” capsules at a dose of 860 mg/kg and 2,580 mg/kg significantly reduced the number of writhing episodes (p < 0.001) compared to the control group. The difference in the number of writhing episodes between the groups using “Dinh Thong Phong” capsules and the group using aspirin at a dose of 150 mg/kg was not statistically significant (p > 0.05).